What works in girls' education : evidence for the world's best investment - Sperling, Gene B. (UPCC book collections on Project MUSE. Political Science and Policy Studies., 2016)
Hard-headed evidence on why the returns from investing in girls are so high that no nation or family can afford not to educate their girls. Gene Sperling, author of the seminal 2004 report published by the Council on Foreign Relations, and Rebecca Winthrop, director of the Center for Universal Education, have written this definitive book on the importance of girls' education. As Malala Yousafzai expresses in her foreword, the idea that any child could be denied an education due to poverty, custom, the law, or terrorist threats is just wrong and unimaginable. More than 1,000 studies have provid.